Efektivitas Fungsi Kepala Desa Dalam Pelaksanaan Pembangunan Di Desa Tompotana Kecamatan Mappakasunggu Kabupaten Takalar - Arlis, Arlis; Razak, Rosdianti; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2020)
This research aimed to study the effectiveness of the function of the village head in the implementation of development in tompotana village, mappakasunggu sub district, takalar regency. This study used qualitative research and support with secondary data. By using di rect observation and interviews with informants, the results of the study showed that the village head in the implementations of this could be seen from the di rection of the goal in which the implementation of village develovment, most of them had achieved the objectives as determined starting from the delivery period. Aspects of the implementation of the development in tompotana village only took approximately one year of implementation and also reached the predetermined target which had started from the aspect of integration of the village head also provided direction to always succeed in development and adjusts what the village head did from every implementation of village development always shrinked with the needs of the community.